The Effect of Thermal Reduction and Film Thickness on fast Response Transparent Graphene Oxide Humidity Sensors. (2016) - Papamatthaiou, S.; Argyropoulos, D.-P.; Farmakis, F.; Masurkar, A.; Alexandrou, K.; Kymissis, I.; Georgoulas, N.
Abstract: Resistive chemical sensors were developed having as sensitive film graphene oxide (GO) spin-coated on glass. Sensor electrical behaviour to room temperature relative humidity was evaluated. High sensitivity characterizes GO sensor. However, it lacks repeatability and long term stability. To this end, we developed spin-coated GO sensors with different active layer thickness, which were subjected to subsequent thermal annealing steps. It was found that the resulting reduced GO (rGO) sensors demonstrate excellent stability compromising, though, the sensitivity which mainly depends on the number of annealing steps and film thickness. Finally, we propose a rapid, transparent, low-power consumption rGO sensor, enabling its use in relevant applications.